Cover Image, Volume 530, Issue 17. Issue 17 (10th October 2022) - Fisher, Karen M.; Garner, Joseph P.; Darian‐Smith, Corinna
Abstract : The cover image is based on the Research Article Small sensory spinal lesions that affect hand function in monkeys greatly alter primary afferent and motor neuron connections in the cord by Karen M. Fisher et al., https://doi.org/10.1002/cne.25395 . Image Credit: Fisher, Garner & Darian‐Smith.